2022
DOI: 10.1002/admi.202200431
|View full text |Cite
|
Sign up to set email alerts
|

Dopant‐Induced Giant Photoluminescence of Monolayer MoS2 by Chemical Vapor Transport

Abstract: Photoluminescence properties of Ti-doped MoS 2 monolayer. a) The PL spectra of Ti-doped and undoped MoS 2 monolayer. Inset shows normalized spectra. b,c) The corresponding integrated PL intensity maps. d) The PL spectra of the pristine and Ti-doped MoS 2 monolayers collected under the excitation of a 532 nm laser after transferred to SiO 2 /Si substrates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…According to a previous report, the photoluminescence quantum yield (PLQY) enhancement of two different radiation processes can be roughly estimated by the following equation [37][38][39]: Here, τ D and τ P correspond to the average exciton lifetime of doped and undoped monolayer MoS 2 , respectively. Based on the previous work of our research group [7], we substituted τ 2 to calculate the PLQY enhancement instead of the average lifetime. The calculated value of η is approximately 1.67, confirming the previously observed phenomenon of PL enhancement after Hf doping.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…According to a previous report, the photoluminescence quantum yield (PLQY) enhancement of two different radiation processes can be roughly estimated by the following equation [37][38][39]: Here, τ D and τ P correspond to the average exciton lifetime of doped and undoped monolayer MoS 2 , respectively. Based on the previous work of our research group [7], we substituted τ 2 to calculate the PLQY enhancement instead of the average lifetime. The calculated value of η is approximately 1.67, confirming the previously observed phenomenon of PL enhancement after Hf doping.…”
Section: Resultsmentioning
confidence: 99%
“…Compared to before doping, the intensity of the PL increased by many times, corresponding to a significant increase in PL intensity. However, due to the large size of rare earth elements, more defects are introduced after doping, resulting in poor crystal quality and lower PL intensity to Ti doping (our research group has previously reported the relevant work [7]). In addition, we also selected Ti [7], Zr as the IVB group element (Figure S3, Supporting Information), and Dy as the rare earth element for the monolayer MoS 2 doping experiments.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations